2020
DOI: 10.1111/jfpp.14678
|View full text |Cite
|
Sign up to set email alerts
|

Post‐harvest quality of sunflower microgreens as influenced by organic acids and ethanol treatment

Abstract: Sunflower microgreens are nutrient‐dense food requiring minimal input but are highly perishable in nature. Low cost, generally regarded as safe (GRAS) chemical treatments (ethanol vapor [EV], citric acid [CA], ascorbic acid [AA], CA + ethanol [CA + E] and CA + AA, distilled water as a control) and packaging in polystyrene trays at 10 ± 1°C was used to extend their shelf life up to 16 days. Electrical conductivity decreased till 4th day and then increased from 4th to 16th day. Control followed by CA + AA had le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…It is worth noting that recent papers dealing with microgreens of some of the oleaginous plants studied in this work, specifically soybean, 43 chia, 44 and sunflower, 45 did not consider the lipid component, including glycerophospholipids. Data obtained for PC and for the other GPL classes in the five oleaginous microgreens considered in the present investigation could thus be compared only with those reported for seeds or eventually for parts of the mature forms of the same plants.…”
Section: Phosphatylcholines (Pc)mentioning
confidence: 99%
“…It is worth noting that recent papers dealing with microgreens of some of the oleaginous plants studied in this work, specifically soybean, 43 chia, 44 and sunflower, 45 did not consider the lipid component, including glycerophospholipids. Data obtained for PC and for the other GPL classes in the five oleaginous microgreens considered in the present investigation could thus be compared only with those reported for seeds or eventually for parts of the mature forms of the same plants.…”
Section: Phosphatylcholines (Pc)mentioning
confidence: 99%
“…On the other hand, radish microgreens stored in the dark had a higher radical scavenging activity and carotenoid retention [18]. Different washing treatments have also been investigated for various microgreens resulting in a significant increase in total phenolics and ascorbic acid during storage [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…During the storage of fruits and vegetables, in order to maintain its own physiological metabolism, the soluble sugar in the fruit will be continuously decomposed and consumed with respiration (Dalal et al, 2020). As shown in Figure 4, the soluble sugar in each group decreased with the increase in storage time.…”
Section: Resultsmentioning
confidence: 99%
“…It can delay the effects of tissue aging and has long been used as a non‐biological preservative disinfectant for preservation of fruits and vegetables, such as apple (Thewes et al, 2021), Chinese bayberries (Wang et al, 2010), and strawberry (Krusong et al, 2015). It has been shown that the ability of ethanol to slow down the ripening process and delay the shelf life of fresh produce depends on the concentration of its application (Dalal et al, 2020). Moreover, ethanol can also inhibit fruit quality loss, reduce fruit decay, improve fruit flavor, and delay fruit and vegetable softening (Han et al, 2010; Ji et al, 2019, 2021).…”
Section: Introductionmentioning
confidence: 99%